The recovery of semen from bath scrunchies. Issue 2 (4th March 2017) - Page, Helen; Harris, Laura; Taylor, Louise; Bishop, Thomas; Newton, Rebecca
Abstract : Despite increased reporting figures for sexual offences, it is believed that this crime type is under-reported. Support information stresses the need to preserve forensic evidence, including the victim not washing themselves/their clothes. The bath scrunchie is a popular choice in the UK as a personal cleaning instrument, and its ability to retain semen was examined in this study. Retention of Acid Phosphatase (AP) and spermatozoa was explored on new and previously used bath scrunchies, in the presence/absence of Dove body wash. Seventy-seven percent of samples were positive for AP and spermatozoa were recovered from 99%, indicating that the bath scrunchie is suitable for recovering this evidence type. Higher spermatozoa recovery was possible from the rope in comparison to the net, as a consequence of differences in surface area, but recovery in the presence of Dove body wash requires further examination, as this was variable. The compactness of the bath scrunchie affected spermatozoa recovery from the net, but did not appear to affect recovery from the rope. These preliminary study results show that the bath scrunchie could be of value as an evidential item if the victim has bathed or showered post-sexual offence and prior to reporting to the Police.